Integrated Analysis Methodology of Applied Projects in the Digital Economy - A. P. Taburchak; S. M. Bychkova; A. A. Butina (Учёт. Анализ. Аудит)
The paper considers the implementing problem of applied projects in the digital economy development. There is substantiated the relevance of applied projects analysis as an innovative component of the digital economy. The methodological basis of the study includes theories of the processes development of informatization and digitalization of the economy. There have been proposed an integrated analysis methodology of applied projects, multicriteria models for calculating the aggregate indicator of four analysis types included in the integrated methodology. Also, there have been developed the principles for calculating aggregate indicators and determined the weight values of each factor. The study proposes the formula for calculation and author’s gradation of the integral indicator of applied projects analysis as the aggregate indicators sum of four analysis types. Based on the analysis results, the company’s top management is able to formulate recommendations on strengthening the bottlenecks of the company for the implementation of applied projects.